Gender Relations in Modern Households: Domestic Labor Divisions in Working Married Couples - Nur Halisah; Huriyah Nahdah Alimah; Kurniati (PT. Nawa Edukasi Nusantara, 2026)
This study discusses gender relations in modern households, focusing on the pattern and factors of domestic labor division between dual-earner couples. The research is motivated by the persistence of patriarchal culture that causes unequal domestic roles despite women’s increasing participation in the public sphere. The aim of this study is to analyze the forms of domestic labor division, the influencing factors, and the efforts to achieve equality within modern households. Using a qualitative descriptive approach through a literature review of academic sources and statistical data, the results indicate that domestic work division is influenced by economic factors, working hours, cultural norms, education level, presence of children, and power relations in the family. Efforts to promote equality include fostering awareness and communication, utilizing household technology, and providing emotional support between partners. In conclusion, gender equality in domestic life can be achieved when husbands and wives build cooperative relationships grounded in justice and compassion as taught in Islam.